At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Our platform connects you with professionals ready to provide precise answers to all your questions in various areas of expertise. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

Match each equation with the correct solution.

A. [tex]\(4(3x + 5) - 3 = 9x - 7\)[/tex]
B. [tex]\(5(x + 7) - 3(x - 4) = 7x + 2\)[/tex]
C. [tex]\(\frac{1}{3}(5x - 9) = 2\left(\frac{1}{3}x + 6\right)\)[/tex]

Solutions:
1. [tex]\( x = \frac{7}{3} \)[/tex]
2. [tex]\( x = -15 \)[/tex]
3. [tex]\( x = -9 \)[/tex]
4. [tex]\( x = 8 \)[/tex]
5. [tex]\( x = 9 \)[/tex]
6. [tex]\( x = -8 \)[/tex]
7. [tex]\( x = -\frac{7}{3} \)[/tex]
8. [tex]\( x = 15 \)[/tex]


Sagot :

Let's solve the given equations one by one and match them to the correct solutions.

1. Equation: 4(3x + 5) - 3 = 9z - 7
- Solution: The x-value that satisfies this equation when expressed in terms of z is [tex]\([\frac{9z}{16} - \frac{7}{2}]\)[/tex]. Notice that this means x is expressed in terms of z. So, there isn't a single numerical value for x, but rather a relationship between x and z.

2. Equation: 5(x + 7) - 3(x - 4) = 7x + 2
- By solving this equation, we find [tex]\( x = 9 \)[/tex].

3. Equation: \frac{1}{3}(5z - 9) = 2\left(\frac{1}{3}z + 6\right)
- Solving for z, we get [tex]\( z = 15 \)[/tex].

Given the results we obtained:
- The equation [tex]\( 4(3x + 5) - 3 = 9z - 7 \)[/tex] pairs with [tex]\( \frac{9z}{16} - \frac{7}{2} \)[/tex].
- The equation [tex]\( 5(x + 7) - 3(x - 4) = 7x + 2 \)[/tex] pairs with [tex]\( x = 9 \)[/tex].
- The equation [tex]\( \frac{1}{3}(5z - 9) = 2\left(\frac{1}{3}z + 6\right) \)[/tex] pairs with [tex]\( z = 15 \)[/tex].

Now, let's match this with the given tiles:

- For the equation [tex]\( 4(3x + 5) - 3 = 9z - 7 \)[/tex]:
- This equation does not have a single numerical x-value in the given options since x depends on z. The solution is [tex]\( \frac{9z}{16} - \frac{7}{2} \)[/tex], but this form matches none of the provided x-values exactly.

- For the equation [tex]\( 5(x + 7) - 3(x - 4) = 7x + 2 \)[/tex]:
- We have [tex]\( x = 9 \)[/tex]. So, match this to [tex]\( x = 9 \)[/tex].

- For the equation [tex]\( \frac{1}{3}(5z - 9) = 2\left(\frac{1}{3}z + 6\right) \)[/tex]:
- We have [tex]\( z = 15 \)[/tex]. So, match this to [tex]\( z = 15 \)[/tex].

Valid matches:
- [tex]\( 4(3x + 5) - 3 = 9z - 7 \)[/tex]: [No direct numerical match]
- [tex]\( 5(x + 7) - 3(x - 4) = 7x + 2 \)[/tex]: [tex]\( x = 9 \)[/tex]
- [tex]\( \frac{1}{3}(5z - 9) = 2\left(\frac{1}{3}z + 6\right) \)[/tex]: [tex]\( z = 15 \)[/tex]

Thus:
- [tex]\( \underline{4(3x + 5) - 3 = 9z - 7 \)[/tex] belongs here}
- [tex]\(5(x + 7) - 3(x - 4) = 7x + 2 \longrightarrow x=9\)[/tex]
- [tex]\( \frac{1}{3}(5z - 9) = 2\left(\frac{1}{3}z + 6\right) \longrightarrow z=15\)[/tex]